Friction losses during slip conditions in regenerative braking of electric vehicles / Agung Prijo Budijono, I. Nyoman Sutantra and Agus Sigit Pramono - Budijono, Agung Prijo; Sutantra, I. Nyoman; Pramono, Agus Sigit (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
The regenerative braking system (RBS) in electric vehicles (EVs) enhances its capability against internal combustion engines (ICE). Antilock braking system (ABS) is widely used in RBS because of its maneuverability and safety. One of the purposes of applying ABS is to avoid slippage. Slip on the braking process, especially hydraulic brakes, results in a difference in time to stop the wheels and the vehicle. It is avoided because it relies on friction between the tires and the road to stop transportation. Timing results showed that ABS with high frequency, above 30 Hz, tended to act like hydraulic brakes. Hydraulic brakes achieved the highest time difference, 8 seconds at 2250 rpm. It increased the distance of 350 m in slipping while the lowest time difference ABS 10 Hz owned, 0.1 seconds at the same rpm. Slips caused losses. These losses could be minimized with low-frequency ABS. It converted the friction between the wheels and the brakes into electrical energy instead of stopping the vehicle. As a result, the 10 Hz ABS had the highest potency stored despite the lowest performance.